2022
DOI: 10.1177/19375867221118675
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Conceptual Framework of Biophilic Design Parameters in Clinical Environments

Abstract: Objectives: To provide a live-experience knowledge base about biophilic design parameters and environmental features to inform policy and design in clinical therapeutic environments. Background: It is increasingly important to review hospital design to make the best use of the affordances of natural elements in supporting both patients’ and staff’s physical and psychological well-being. The biophilic design theory provides an appropriate design approach. However, current biophilic design frameworks fail to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…A narrative literature review, a systematically searched literature review, and a meta-synthesis analysis informed the scientific evidence using secondary sources, while professional practice and experience were investigated with primary data collected from semi-structured interviews. The separate findings from the meta-synthesis (Study 1) ( 36 ) and the systematically searched review (Study 2) ( 37 ) have been extensively discussed in two published articles, so this paper primarily focuses on how the outcomes of these two studies, together with the data obtained from the semi-structured interviews with practitioners (Study 3), generated the final framework as a design system.…”
Section: Methodsmentioning
confidence: 99%
“…A narrative literature review, a systematically searched literature review, and a meta-synthesis analysis informed the scientific evidence using secondary sources, while professional practice and experience were investigated with primary data collected from semi-structured interviews. The separate findings from the meta-synthesis (Study 1) ( 36 ) and the systematically searched review (Study 2) ( 37 ) have been extensively discussed in two published articles, so this paper primarily focuses on how the outcomes of these two studies, together with the data obtained from the semi-structured interviews with practitioners (Study 3), generated the final framework as a design system.…”
Section: Methodsmentioning
confidence: 99%
“…1. Prehistoric Era: Indigenous communities worldwide demonstrate early biophilic design by integrating natural elements like wood and stone into their dwellings for optimal sunlight and ventilation [38,39].…”
Section: Timeline Of Biophilic Designmentioning
confidence: 99%
“…Similarly, Gola et al (2021) found that a short break in green spaces was associated with improved mental and psychophysical well-being (mood), including fatigue. There is a growing body of evidence on the positive effects of nature, landscaping, greenery, and views to the outside on healthcare providers, patients, families, and even the reputation of the hospital itself (Allahyar & Kazemi, 2021; Elantary et al, 2021; Iqbal & Abubakar, 2022; Kim, 2021; Martin et al, 2021; Naomi, 2020; Tekin et al, 2022).…”
Section: Healthcare Provider Restoration (Respite and Breakrooms)mentioning
confidence: 99%